What are we Really Aiming for? Identifying Concrete Student Behavior in Co-Regulatory Formative Assessment Processes in the Classroom - Gulikers, Judith; Veugen, Marijke; Baartman, Liesbeth (Frontiers in Education, 2021)
Formative assessment has the potential to incite co-regulatory activities that foster students’ development of self-regulatory skills. Teacher often intend to use formative assessment to foster self-regulation. However, this requires purposeful interaction between students and teachers. To improve co-regulatory formative assessment implementation, research and professional development needs to pay attention to what co-regulatory formative assessment look like. This participatory study explores if and how the process of formative assessment – described in five phases of the formative assessment cycle (Authors, 2017; 2021) – facilitates teachers to explicate concrete student and teacher behavior in their formative classroom that intends to stimulate self-regulated learning. Teachers of a longitudinal formative assessment professional development project participated in three activities in which a variety of data was collected. The results show that using the five phases of the formative assessment cycle helps to concretize co-regulatory formative assessment behavior that relates to various phases of regulation. They also show that starting from a student perspective, explicating expected student behavior and using this to explicate related teacher behavior, challenges teachers’ formative assessment intentions and implementations. The activities make teachers realize the importance of purposefully designing co-regulatory formative assessments. Teachers explicated examples describe actual student-teacher co-regulatory interactions in the formative classroom and they are found to differ in the extent to which they are teacher-directed or student-directed. This challenges our thinking on the co-regulation processes incited by formative assessments and how this can stimulate students to develop self-regulatory skills.